KERENTANAN SOSIAL TERHADAP BANJIR DAN ASET PENGHIDUPAN MASYARAKAT BANTARAN SUNGAI BENGAWAN SOLO KOTA SURAKARTA PASKA RELOKASI MANDIRI - , agustina setyaningrum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In 2007 high rainfall was occurred and led to flood triggered by overflowing of Bengawan Solo River in Surakarta urban areas. People are permitted to choose their own relocation sites either individually or collectively, scattered in Surakarta, Sukoharjo, and surrounding.. The aims of this study are to assess the level of social vulnerability of the community who relocated to new place, to assess the livelihood assets of the community after relocation and to arrange strategies to minimize vulnerability of flood hazard. The data used in this study consist of primary data and secondary data. Sample was taken based on probability sampling. Proportionate stratified random sampling is chosen because each study area has different numbers of populations therefore the number of samples are taken differently for each areas. The results of the SMCE showed that there are still area that are included in high and moderate social vulnerability. High social vulnerability is caused by the density of buildings, the amount of non-productive population, number of poor families, income level, distance from the river to the settlement, and history of the disaster. Community living on high vulnerability area, have relatively lower capital primarily to finance capital. People who live in moderate vulnerability have progressive position and they will be able to cope threats to flooding with all they have. People who live in high vulnerability have a survive position, which condition of high vulnerable area is very weak and has many challenges. They are vey weak and have a lot of challenges. Internal factors must be fixed first and then has to endure to anticipate the hazard that may occur. Keywords: Vulnerability, Relocation, Livelihood